Public health workforce management during a major organizational reform in the World Health Organization African Region Country Offices - Rwamatwara, Egide; Usman, Abdulmumini; Salla Ba, Ndoungou; Kabore, Patrick; Kulausa, Hyelni; Olu, Olushayo Oluseun; Gasasira, Alex; Cabore, Joseph; Moeti, Matshidiso (Frontiers in Public Health, 2025)
Following her appointment as Regional Director of the World Health Organization African Region in February 2015, Dr. Matshidiso Moeti launched the Transformation Agenda to reform and align the organization’s work with regional public health needs. This initiative was prompted by the weaknesses observed during the 2013–2014 Ebola virus disease outbreak in West Africa, particularly delayed response and limited availability of skilled personnel for rapid detection and management. A key component of the agenda was the functional review of the 47 World Health Organization country offices in the region, aimed at optimizing structures and staffing to be fit-for-purpose. Conducted between 2017 and 2023, the functional review sought to tailor the country office capacities to the specific health priorities of all 47 Member States and introduce more effective operational models. This paper examines the management of human resources throughout the functional review process, with a focus on workforce challenges, including anxiety, stress, and uncertainty and the strategies adopted by organization to mitigate their impact. It also reviews the steps taken to strengthen country offices human resource capacities in line with the functional review objectives and draws attention to the challenges, good practices, and lessons learned in managing organizational change during institutional reform.